Instructivo de procedimiento para pruebas a barrajes conectados en subestaciones eléctricas. (2022)
Preventive maintenance in an electrical substation is of the utmost importance for its optimal functioning, avoiding stoppages due to equipment failure which produce economic losses to companies due to service interruption; The purpose of 2 this work is to prepare the procedure instructions for the tests that are carried out in the electrical substations to the barrages connected to the network, using the current and voltage injection method, these tests are carried out at the beginning of the commissioning of the substation or to check its operation after a maintenance shutdown. The instructions establish the methodology that must be applied to carry out the necessary tests on connected busbars in an electrical substation, complying with the electrical safety standards for personnel, equipment, and the environment.